A two-phase interactive solution method for multiple-objective programming problems - Buchanan, J. (IEEE transactions on systems, man, and cybernetics, 1991)
There has been increasing emphasis on interactive methods for the solution of multiple objective programming (MOP) models. These solution methods are commonly founded on economic definitions of rationality and assume the existence of a well-defined, stable utility function. A two-phase solution method that is behaviorally founded and draws on the literature about the structure of MOP models is considered. Some relevant behavioral issues are discussed, and a solution approach that integrates the more structural MOP research with a proven behavioral model of human decision-making is presented. The method seeks to accommodate the behavioral characteristics of human decision-making situations. An example of the solution method for the group decision-making situation is given.< >